Institutional accreditation in medical education: The experience of the survey visit teams - Mohammad H Yarmohammadian; Elahe Khorsani; Roohangiz Norouzinia; Samaneh Mirzaei; Soheila Ehsanpour; Nikoo Yamani; Fatemeh Rezaei (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVES: This study discussed about challenges and opportunities of institutional accreditation in Iranian medical universities. The lesson learned of the first round of the accreditation would direct initiatives and solutions for future accreditation. METHODOLOGY: This research is a qualitative content analysis research that studied the experience of the survey visit teams. Semistructured interviews with a purposive sampling approach were done to reach data saturation. Constant comparative method was used to analyze the data. RESULTS: The emergent themes were incompatible scheduling with accreditation workload, accreditation sustainability, the weakness of the survey instrument, advantage of the survey instrument, the quality of evaluators' survey, the opportunity of progress for universities, accreditation perspective, defendable cost opportunity, perceived injustice, and the leading strategies. In this study, the relationship between categories and themes was shown with a systematic approach. CONCLUSION: In medical education systems, it is necessary to continue the research and development studies using the findings in each accreditation period to achieve the prospect of international accreditation.